PENGEMBANGAN DESAIN PERMAINAN BERBASIS ADVENTURE EDUCATION DALAM KEMAMPUAN KOMUNIKASI DI KELAS 5 SEKOLAH DASAR - Sri Aprilia, Arifina; Ardiyanto, Asep; Fita Asri Untari, Mei (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Adventure is an interesting and challenging activity, such as engaging in explorative activities that uncover new things never previously discovered. Education is a learning process aimed at developing students' potential and improving the learning process. Communication skills refer to a process of interaction or reciprocal relationships between individuals who send and receive messages from one another. Based on this research, after students received an adventure-education-based game design, they became more interested in enhancing their communication skills. SDN 2 Cepokomulyo achieved a 90% interest rate, SDN 2 Triharjo reached 94%, and SDN 1 Sojomerto reached 95%. From this, it can be concluded that these elementary students are highly interested in learning activities developed using adventure-education-based games, making this approach highly effective.